Carbonylation catalysts based on metal complexed PAMAM-dendrimers supported on mesoporous and periodic mesoporous silica supports - Reynhardt, Jan Petrus Karel (University of Ottawa (Canada), 2005)
This thesis describes the synthesis and characterization of various polyamidoamine (PAMAM) dendrimer moieties supported on amorphous mesoporous and periodic mesoporous silica supports. The surface characteristics of the supports are investigated using various methods and found to be intricately involved in the success of the dendrimer synthesis. The dendrimers are phophinomethylated and complexed with either palladium or rhodium and used as catalysts for carbonylation reactions. The palladium complexed C6-PAMAM dendrimers supported on aminopropyl silica gel are recyclable catalysts for the hydroesterification of olefins and turnover numbers (TON) of up to 1200 are possible. C2-PAMAM dendrimers supported on LPMCM-41 and Davisil are complexed with rhodium and used as catalysts for the hydroformylation reaction of olefins. These catalysts show how the pore geometry influences the activity and recyclability of the catalysts. The dendrimer-rhodium complexes supported on LPMCM-41 exhibit very high activity and a TOF of up to 1800 h-1 are observed for the hydroformylaton of 1-octene. These catalysts can be recycled effectively by simple filtration. A negative dendrimer effect is observed with the higher generations exhibiting lower activity than the lower generations. The dendrimer-rhodium complexes supported on Davisil also exhibit very high activity and a TOF of up to 1700 h-1 are observed for the hydroformylation of 1-octene. The activity of these catalysts are less dependent on the generation than the LPMCM-41 dendrimers, and excellent activity is observed up to the third generation for the hydroformylation reaction of 1-octene.
Keywords: Chemistry, General.